Bibliometric analysis of publications on necroptosis from 2001 to 2021 - Liu, Yang; Zhou, Xiaojiang; Wang, Fangfei; Liu, Cong; Xie, Jun; Guan, Le; Xie, Yong (Frontiers in Cell and Developmental Biology, 2022)
Background: Necroptosis plays an important role in inflammation, cancer, and neurodegenerative diseases. In recent years, the number of studies related to necroptosis has increased and research has become increasingly in-depth. This study aimed to summarize the research conducted since 2001 to discover hotspots and trends in the field of necroptosis. Methods: The Web of Science Core database was used to identify global publications on necroptosis from 2001 to 2021. Bibliometric analysis was performed using Rstudio, VOSviewer, and CiteSpace. Results: The number of publications related to necroptosis gradually increased from 2001 to 2021. Vandenabeele P had the most publications at 45. Yuan JY had the most citations at 5,901. Necroptosis research has been dominated by China and Chinese institutions. Cell Death and Disease had the highest number of related publications among the examined journals. Seven of the top 10 most cited papers had more than 500 citations. Necroptosis, cell death, autophagy, injury, cancer, activated B cell nuclear factor kappa-light chain enhancer, and oxidative stress were important keywords in keyword analysis. Recent research has increasingly focused on breast cancer, receptor-interacting serine/threonine protein kinase 1, modulation, pseudokinase mixed lineage kinase domain-like protein, membrane, protection, and cycle. Conclusion: Interest in necroptosis-related research continues to increase steadily, and there is close cooperation between countries and institutions in the field of necroptosis. The study of necroptosis-related molecules and mechanisms, and the relationship between necroptosis and cancer, may be hotspots and directions in future research.